Large-Scale Identification of Gibberellin-Related Transcription Factors Defines Group VII ETHYLENE RESPONSE FACTORS as Functional DELLA Partners . Issue 2 (12th August 2014) - la Rosa, Nora Marín-de; Sotillo, Berta; Miskolczi, Pal; Gibbs, Daniel J.; Vicente, Jorge; Carbonero, Pilar; Oñate-Sánchez, Luis; Holdsworth, Michael J.; Bhalerao, Rishikesh; Alabadí, David; Blázquez, Miguel A.
Abstract : Transcription factors of the APETALA2 superfamily are regulated by DELLAs which represents a cross regulatory node for gibberellins and ethylene to control apical hook opening . Abstract: DELLA proteins are the master negative regulators in gibberellin (GA) signaling acting in the nucleus as transcriptional regulators. The current view of DELLA action indicates that their activity relies on the physical interaction with transcription factors (TF s). Therefore, the identification of TF s through which DELLAs regulate GA responses is key to understanding these responses from a mechanistic point of view. Here, we have determined the TF interactome of the Arabidopsis ( Arabidopsis thaliana ) DELLA protein GIBBERELLIN INSENSITIVE and screened a collection of conditional TF overexpressors in search of those that alter GA sensitivity. As a result, we have found RELATED TO APETALA2.3, an ethylene-induced TF belonging to the group VII ETHYLENE RESPONSE FACTOR of the APETALA2/ethylene responsive element binding protein superfamily, as a DELLA interactor with physiological relevance in the context of apical hook development. The combination of transactivation assays and chromatin immunoprecipitation indicates that the interaction with GIBBERELLIN INSENSITIVE impairs the activity of RELATED TO APETALA2.3 on the target promoters. This mechanism represents a unique node in the cross regulation between the GA and ethylene signaling pathways controlling differential growth during apical hook development.